A Six-year Image-subtraction Light Curve of SN 2010jl. (12th April 2019) - Ofek, E. O.; Zackay, B.; Gal-Yam, A.; Sollerman, J.; Fransson, C.; Fremling, C.; Kulkarni, S. R.; Nugent, P. E.; Yaron, O.; Kasliwal, M. M.; Masci, F.; Laher, R.
Abstract: SN 2010jl was a luminous Type IIn supernova (SN), detected in radio, optical, X-ray and hard X-rays. Here we report on its six-year R - and g -band light curves obtained using the Palomar Transient Factory. The light curve was generated using a pipeline based on the proper image-subtraction method and we discuss the algorithm performances. As noted before, the R -band light curve, up to about 300 days after maximum light is well described by a power-law decline with a power-law index of α  ≈ −0.5. Between day 300 and day 2300 after maximum light, it is consistent with a power-law decline, with a power-law index of about α  ≈ −3.4. The longevity of the light curve suggests that the massive circumstellar material around the progenitor was ejected on timescales of at least tens of years prior to the progenitor explosion.